Towards a Model to Predict the Size and Shape of Port Hinterlands. - Cooke, Alan Charles Upton (My University, 1965)
This thesis argues that a theoretical approach to the study of the size and shape of port hinterlands is required if we are to know what factors affect this phenomenon. Following a review of the literature dealing with port hinterlands, a model is devised to predict the location of port hinterlands. This model uses data neither of actual commodity movements nor of port clearances as variables to explain the size and shape of port hinterlands, and uses instead only those factors that are constant or predictable. The reason for this decision is that the commodity data can give us only the hinterlands of the past whereas we are interested as much in the hinterlands of the present and the near future.
Keywords: Geography